Position of Supervisory Board Organ and Its Implications for the Institutional Corruption Eradication Commission - Muh Rinaldy Bima; Rizki Ramadani (LAW REFORM, 2020)
The negative view that the People's Representative Council of Indonesia (DPR) has long been in a constant effort to weaken the Corruption Eradication Comission (KPK), making the revision process of the KPK law until after it is legalized, receives pro and contra. A number of provisions in the new Law of KPK are considered to potentially weaken the independence of the institution, especially concerning the establishment of the so called Supervisory Council. The purpose of this research was to analyze an the position of the Supervisory Council and to explain its implications on the institutional aspects of the KPK.This normative legal research was conducted through a literature study using conceptual and statue approaches, which then analyzed qualitatively. The results show that the new Law of KPK makes the Supervisory Council as an internal supervision organ, but its position had not well formulated yet in the institutional structure. The existence of the Supervisory Council also have some impacts on the institutional aspects of KPK in terms of Institutional and functional independences.